Investigating environmental life cycle impacts of active living wall for improved indoor air quality - Mehzabeen Mannan (16442001) (2022)
Life-Cycle Assessment (LCA) is the systematic analysis of the potential environmental impacts of any product or process throughout the life cycle. This work presents the LCA of Active Living Wall System (ALW), an advanced form of living wall, which is a vertical greening system designed to reduce the indoor air pollutants along with several other benefits for occupants and building environment. Although this system is considered as having high potential to improve indoor air quality, ALW has not yet been assessed thoroughly from environmental perspective. Hence, the environmental impacts of production, operation, maintenance, and finally disposal phases of ALW systems have been investigated through LCA in this paper. Built as an experimental set-up, two different ALW systems have been investigated extensively for this study including ALW system based on felt layers, and planter box ALW. Life-cycle environmental impacts have been analyzed using ReCiPe environmental impact methodology. Comprehensive study results showed similar environmental burden for both ALW systems for a life span of 10 years, indicating stainless steel and PVC as the most impacting construction materials. Operational energy was responsible for major impacts in climate change and terrestrial acidification category where incorporation of solar energy showed possible reduction of burden. Although having few limitations, this LCA study has the potential to help both the manufacturers and built environment experts to improve the balance between benefits and environmental impacts for a more sustainable ALW system that can ultimately lead us to an improved indoor environment. Other Information Published in: Building and Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.buildenv.2021.108595